RECONCEPTUALISING BNPL ADOPTION USING AN EXTENDED TPB FRAMEWORK WITH FINANCIAL LITERACY AND BEHAVIOURAL OUTCOMES - Jamil, Afzal Hossain; Basri, Mohd Faizal (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
This paper proposes a conceptual framework that integrates the Theory of Planned Behaviour (TPB) with financial literacy and behavioural finance to explain BNPL usage in Malaysia. Attitude, subjective norms, and perceived behavioural control influence usage intention, moderated by financial literacy. Post-adoption outcomes i.e. impulse buying and financial stress are incorporated to address critical gaps in the literature. Eight research propositions are developed for empirical testing. The model provides a theoretically grounded and contextually appropriate explanation of BNPL behaviour, particularly in settings characterised by low financial literacy and widespread digital access. It advances fintech research by linking cognitive, motivational, and behavioural constructs within a unified analytical framework. The framework offers practical insights for regulators concerned with consumer protection, educators designing financial literacy initiatives, and BNPL providers seeking more ethical product development. It also lays the groundwork for empirical studies employing moderated regression or structural equation modelling to examine the evolving dynamics of digital credit usage.